Jahanara Shahnawaz: South Asian politician, feminist and writer - Hasan, Md. Mahmudul (Prothon Alo, 2025)
Jahanara Shahnawaz was born into the illustrious Mian (or Arain) family of Lahore. Another woman of comparable stature in the region is Shaista Ikramullah (1915–2000) who was also born into a preeminent political dynasty – the Suhrawardy family of Bengal. These two women navigated their way through the political landscape and carved out a niche for themselves in a patriarchal domain, and thus they may serve as role models for present-day women activists.